Pengaruh Kompetensi Pedagogik Guru Dalam Meningkatkan Mutu Pembelajaran Siswa - Marshavira Pricilia; Febrianti Febrianti; Fikri Fadilatul Ikhsan; Meisya Indah Putri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This article discusses the important role of teacher pedagogical competence in improving the quality of student learning processes. Educators who can organize learning, understand student characteristics, design and carry out learning, and evaluate learning outcomes can have a significant impact on the quality of education. Researchers use qualitative methods. How to look at the problem of the importance of pedagogic competence to improve the quality of learning in education. The author collected data for this article from a literature review of various sources from books, magazines, journals, the internet, and others. By referring to established pedagogical competency standards, this article will help teachers improve the quality of learning by developing learning tools, professional competencies, good character and social communication skills with the community around the school. Improving the quality of student learning can be achieved through integrated efforts to develop teacher pedagogical competence which is the key to the success of the education system.